Modul Pembelajaran Berbasis Flipbook Digital: Upaya Meningkatkan Regulasi Diri pada Siswa SMA - Sri Ratna Sari; Muhammad Nursa’ban; Rino Lengam (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Advances in educational technology demand innovations in teaching materials that can foster self-regulation in students as an essential 21st-century skill. Evidence shows that high school students still face difficulties in managing their motivation and independence in learning, while conventional teaching materials do not fully support these needs. This study aims to develop and test the effectiveness of flipbook-based digital learning modules in improving self-regulation in the subject of soil formation and soil distribution for 10th grade students. The test subjects included 10th grade high school students and teachers. The method used was the ADDIE model combined with a quasi-experimental pretest-posttest control group design involving 36 students in the experimental group and 36 students in the control group. The research instruments included expert validation, a Zimmermen indicator-based self-regulation questionnaire, learning outcome test questions, observation sheets, and interview guidelines. Data analysis was conducted quantitatively using feasibility percentages, independent sample t-tests, and N-Gain, as well as qualitatively using the Miles & Huberman model. The results of expert validation of the media and materials showed a category of “highly feasible,” while the responses of students and teachers were in the “very positive” category. The results of the independent t-test showed a significant difference between the experimental and control groups, while the N-Gain test showed an increase in self-regulation in the “moderate” category. This study implies that digital flipbook modules can be a practical and effective innovative alternative to support learning transformation and strengthen self-regulation in high school students.